2001
DOI: 10.1002/1521-3765(20010518)7:10<2134::aid-chem2134>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Mechanism of the Oxidative Addition of Phenyl Iodide to Pd0 Ligated by Triphenylarsine: Evidence for the Formation of a T-Shaped Complex [PhPdI(AsPh3)] and for the Decelerating Effect of CH2=CH−SnBu3 by Formation of [Pd0(η2-CH2=CH−SnBu3)(AsPh3)2]

Abstract: The oxidative addition of phenyl iodide to the palladium(o) generated from [Pd0(dba)2] and n equivalents of AsPh3 (the most efficient catalytic precursor in Stille reactions) proceeds from [(solv)Pd0(AsPh3)2] (solv= solvent). However, the latter is present only in trace concentrations because it is involved in an equilibrium with the major, but nonreactive, complex [Pd0(dba)(AsPh3)2]. As regards the phosphine ligands, dba has a decelerating effect on the rate of the oxidative addition by decreasing the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 20 publications
10
67
0
5
Order By: Relevance
“…In that range, the H ortho proton of the metallated phenyl (near 7 ppm) and the H para and H meta protons (near 6.5 ppm, partially overlapped with each other), are observed. As reported in the literature,8 [PdPhI(AsPh 3 ) 2 ] ( 8 ) gives rise in CDCl 3 to two sets of signals corresponding to two different chemical species (Figure 3 a). Similar behavior (with a smaller proportion of the minor signal) is observed for [PdPhCl(AsPh 3 ) 2 ] ( 7 ) (Figure 3 b).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…In that range, the H ortho proton of the metallated phenyl (near 7 ppm) and the H para and H meta protons (near 6.5 ppm, partially overlapped with each other), are observed. As reported in the literature,8 [PdPhI(AsPh 3 ) 2 ] ( 8 ) gives rise in CDCl 3 to two sets of signals corresponding to two different chemical species (Figure 3 a). Similar behavior (with a smaller proportion of the minor signal) is observed for [PdPhCl(AsPh 3 ) 2 ] ( 7 ) (Figure 3 b).…”
Section: Resultssupporting
confidence: 64%
“…The major species in each spectrum is [PdPhX(AsPh 3 ) 2 ]. The minor species in the solution of 8 was attributed in the literature to the so‐called T‐shaped [PdPhI(AsPh 3 )(S)],8 but this is not correct. The signals of the minor species correspond to the only signals observed in the CDCl 3 solutions of the corresponding dimers [( μ ‐X) 2 Pd 2 Ph 2 (AsPh 3 ) 2 ] (X=Cl ( 9 ), I ( 10 )), and are in fact the unchanged dimers.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…These studies were based on kinetic measurements of the palla- [50,149]. This study revealed that, under those conditions, the species preceding the transmetallation steps is complex 61, bearing a DMF as a ligand (Scheme 1-27).…”
Section: Dissociative Mechanistic Proposalsmentioning
confidence: 71%
“…This result is in contrast to the better transmetallation ability reported for vinyl respect to phenyl group [26]. However, it has been demonstrated that a nucleophile such as n Bu 3 SnCH@ CH 2 , which is able to coordinate Pd(0) species, causes in some catalytic systems the formation of new palladium complexes that do not react with the substrate [27]. Among the tested aryl bromides, bromobenzene was the less reactive: the reaction with n Bu 3 SnPh carried out at 120°C stopped at a 38% yield in biphenyl (entry 12-2).…”
Section: Resultsmentioning
confidence: 99%